(3GdEgdjLjIs - (3CHh YHO Gddg, LYaQ GdUGObs ((3GdfLas)
(3ChdgG (B:s
(3bGd cJH GdeaVd Hf YeQ GdLYaj Edi CHj YHO Gddg LYaQ Hf eMeO GdUGOb jYdeg Cf CbhGeG XgQhG ef Cgd gPg GdedI jLMOhf GdQHhHjI(B... (3acJH CHh YHO Gddg Ydjg GdSdGe CeG HYO habfG Gddg hEjGc(B...s
(3BNQgG (B:s
(3ajchf HdG JYH hdG cja bGd bO HdZJ MSHc hgj aj gPg cGajI def Ybd(B.s
(3QhGjI GdeaVd Hf YeQ GdLYajs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJhMjO hGdedd hGdfMds